2006
DOI: 10.1021/ja058077g
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic, Enantioselective [4 + 2]-Cycloadditions of Ketene Enolates and o-Quinones:  Efficient Entry to Chiral, α-Oxygenated Carboxylic Acid Derivatives

Abstract: We report catalytic, enantioselective [4 + 2]-cycloadditions of o-quinones with ketene enolates (derived from readily available acid chlorides) using cinchona alkaloid derivatives as catalysts to produce products in high enantiomeric excess (ee) and good to excellent yields. The thermodynamic driving force for these reactions is due in part to the restoration of aromaticity to the products. The resulting chiral, bicycloadducts can be synthetically manipulated in a variety of useful ways, for example to provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(41 citation statements)
references
References 6 publications
(7 reference statements)
0
39
0
2
Order By: Relevance
“…[90] Lewis base catalysis has also made possible the first [4+2] cycloaddition of a ketene with an oquinone 58, again through the intermediacy of a similar amidonium enolate. [91] Cleavage of 59 affords high yields of enantioenriched a-hydroxycarboxylic acid derivatives. The reactions of ketenes are not broadly representative of n-p* type activation because the n-p* interaction need not necessarily lead to both enhanced electrophilic and nucleophilic character of the intermediate.…”
Section: Lewis Base Catalyzed Reactions Of Ketenesmentioning
confidence: 99%
“…[90] Lewis base catalysis has also made possible the first [4+2] cycloaddition of a ketene with an oquinone 58, again through the intermediacy of a similar amidonium enolate. [91] Cleavage of 59 affords high yields of enantioenriched a-hydroxycarboxylic acid derivatives. The reactions of ketenes are not broadly representative of n-p* type activation because the n-p* interaction need not necessarily lead to both enhanced electrophilic and nucleophilic character of the intermediate.…”
Section: Lewis Base Catalyzed Reactions Of Ketenesmentioning
confidence: 99%
“…[90] Unter Lewis-Base-Katalyse gelang auch die erste [4+2]-Cycloaddition eines Ketens mit einem ortho-Chinon, 58, die wieder über ein ähnliches Amidoniumenolat als Zwischenstufe verlief. [91] Die Spaltung von 59 führte mit hohen Ausbeuten zu enantiomerenangereicherten a-Hydroxycarbonsäure-Derivaten. [94] Dennoch verlaufen diese Reaktionen langsam, sodass brauchbare Umsätze oft erst nach Tagen erreicht werden.…”
Section: Umfang Des Aufsatzesunclassified
“…
Abstract: A straightforward synthesis of optically active trifluoromethyl dihydropyranones and spirocyclic oxindole-dihydropyranones has been realized by the chiral N-heterocyclic carbenes-catalyzed cy-A C H T U N G T R E N N U N G clization of a,b-unsaturated b-methylacyl chlorides with activated trifluoromethyl ketones or isatin derivatives.Keywords: asymmetric catalysis; cyclization; dihy-A C H T U N G T R E N N U N G dropyranones; N-heterocyclic carbenes; organocatalysis; vinylketenes Since Staudingers discovery of ketenes and the cycloaddition of ketene with imines to form b-lactams in early 1900s, [1] the cycloaddition reactions of ketene have become one of the powerful methodologies for construction of cyclic compounds.[2] In last decades, the catalytic enantioselective [2 + 2] or [2 + 4] cycloaddition of ketenes with aldehydes, [3] imines, [4] azo compounds, [5] nitro compounds, [6] oxadienes, [7] and azadienes [8] had been well established. In 2008 and later, we, [9] independently with Smith et al, [10] have demonstrated that N-heterocyclic carbenes (NHCs) [11] were efficient catalysts for the formal cycloaddition reactions of ketenes.
…”
mentioning
confidence: 99%